Human mobility restrictions and inter-provincial migration during the COVID-19 crisis in China. Issue 1 (1st January 2021) - Li, Angran; Liu, Zhen; Luo, Mengsha; Wang, Yan
Abstract: The governmental responses to coronavirus disease 2019 (COVID-19) pandemic, including the approach, interventions, and their associated effectiveness, vary across social, cultural, political, and institutional contexts. In China, the Wuhan lockdown significantly reduced the transmission of COVID-19 throughout the country. Chinese central and local governments' responses to disease containment and mitigation were uniform in policymaking but implemented differently across local governing contexts. This study examines the variation in the effects of human mobility restrictions on inter-provincial migration flow during the COVID-19 outbreak in China. The results show that mobility restrictions reduced the inter-provincial in-migration flow by 63%, and the out-migration flow by 62% from late January to early May in 2020, but the effects varied significantly across provinces. Further, the negative effects of mobility restrictions on province's outflow migration were greater in provinces where local governments had higher levels of social media involvement, greater public security spending, and longer duration of first-level response to public health emergencies. The finding provides important insights for understanding China's local governmental responses to mobility restrictions and their effects on the spread of COVID-19.